2009
DOI: 10.1111/j.1365-3156.2009.02267.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics and paediatric acute respiratory infections in rural Vietnam: health‐care providers’ knowledge, practical competence and reported practice

Abstract: Summaryobjective To assess knowledge, practical competence and reported practices among health-care providers about antibiotics to treat acute respiratory infections in children under five in rural Vietnam.method Health-care providers prescribing or dispensing western drugs for children self-completed a structured questionnaire. Recommendations concerning antibiotic use from WHO and national guidelines were used to assess the appropriateness of reported treatment of acute respiratory infections.results Ninety-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
37
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 32 publications
6
37
1
Order By: Relevance
“…Thus, the public knowledge, attitude and practice towards antibiotic use in China warrant greater attention. Besides surveys on the general public, a number of studies have also focused on different cohorts of populations including nurses of day-care centers, parents with infants, internal medicine specialists, dentists and workers in pharmacies [13-17] and others targeting medical students and interns [18-20]. …”
Section: Introductionmentioning
confidence: 99%
“…Thus, the public knowledge, attitude and practice towards antibiotic use in China warrant greater attention. Besides surveys on the general public, a number of studies have also focused on different cohorts of populations including nurses of day-care centers, parents with infants, internal medicine specialists, dentists and workers in pharmacies [13-17] and others targeting medical students and interns [18-20]. …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, for the STI arm, an alternative version of the questionnaire was constructed with the STI section first, followed by the ARI part. The ARI section of the questionnaire was created contextually through previous studies in the same environment [18] and also using World Health Organization (WHO) IMCI guidelines [16,23]. It included two parts: (i) knowledge about etiology and antibiotic use for ARI symptoms among children under five; (ii) clinical scenarios examining practical competence related to the management of children under five with ARIs.…”
Section: Methodsmentioning
confidence: 99%
“…Antibiotics are frequently dispensed or prescribed in drug stores, commune health stations or private clinics, often without an appropriate indication [1820]. It has been reported that most HCPs prescribe or dispense antibiotics for common colds and only 19% had knowledge compliant with the recommended guidelines.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations